LEARNING STRATEGY IMPLEMENTATION OF GENERATIVE LEARNING ASSISTED SCIENTIST’S CARD TO IMPROVE SELF EFFICACY OF JUNIOR HIGH SCHOOL STUDENT IN CLASS VIII - Yuliarti, R.; Khanafiyah, S.; Darmaputra, N. M. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
In general, self-efficacy of the students is still low. This study aims to determine the learning strategies implementation of generative learning assisted scientist's card in improving self-efficacy and cognitive learning outcomes of the students. The study designed form One Group Pretest-Posttest Design. The improvement of self-efficacy can be determined from the change in the questionnaire score before and after the learning and observations during the learning process. Cognitive learning outcomes are known from pretest and posttest scores. To determine the improvement, the data were analyzed by using the gain test. The results showed that N-gain of self-efficacy is 0.13 (low) and N-gain of cognitive learning is 0.60 (medium). Based on the observation, students’ self-efficacy has increased each meeting. Cognitive learning results also achieved mastery learning as big as 72.88%. It could be concluded that the learning strategy of generative learning assisted scientist's card can improve self efficacy and cognitive learning outcomes of the students.Pada umumnya, self efficacy yang dimiliki siswa masih rendah. Penelitian ini bertujuan untuk mengetahui penerapan strategi pembelajaran generative learning berbantuan scientist’s card dalam meningkatkan self efficacy dan hasil belajar kognitif siswa. Desain penelitian berbentuk One Group Pretest-Posttest Design. Peningkatan self efficacy dapat diketahui dari perubahan skor angket sebelum dan sesudah pembelajaran dan hasil observasi selama pembelajaran. Hasil belajar kognitif diketahui dari skor pretest dan posttest. Untuk mengetahui peningkatannya, data yang diperoleh dianalisis menggunakan uji gain. Hasil penelitian menunjukkan bahwa peningkatan self efficacy berkatagori rendah dan peningkatan hasil belajar kognitif berkatagori sedang. Berdasarkan hasil observasi, self efficacy siswa setiap pertemuan meningkat. Hasil belajar ranah kognitif juga mencapai ketuntasan belajar .Jadi dapat disimpulkan bahwa strategi pembelajaran generative learning berbantuan scientist’s card dapat meningkatkan self efficacy dan hasil belajar ranah kognitif siswa.